(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The Advisory Opinion of the International Court of Justice of 19 July 2024 on the Legal consequences arising from the policies and practices of Israel in the Occupied Palestinian Territory, including East Jerusalem The International Court of Justice’s advisory opinion of 19 July 2024 was issued at a tragic turning point in the Middle East crisis, but it does not deal with the attack of 7 October 2023 or with the consequences that the Israeli reaction is provoking in the Gaza Strip. Rather, it considers the policies and practices of Israel in the Occupied Palestinian Territory (OPT) from 1967 onwards, with particular reference to the West Bank and East Jerusalem. This article concentrates on three conclusions reached by the ICJ in that opinion: the first pertains to the status of the Gaza Strip, which the Court deems to be subject to the law of occupation, even today; the second is the determination of the unlawfulness of the continued presence of Israel in the OPT, due to the annexation policy pursued by Israel in East Jerusalem and the West Bank, in violation of the jus ad bellum and Palestinian self-determination; the third concerns the finding that Israeli policies in the OPT amount to segregation of the Palestinian population. While underlining the importance of the Court’s findings, we highlight some limits and flaws in the ICJ’s legal reasoning.